Relationship Between Excessive Gestational Weight Gain and Neonatal Adiposity in Women With Mild Gestational Diabetes Mellitus. Issue 6 (December 2016) - Blackwell, Sean C.; Landon, Mark B.; Mele, Lisa; Reddy, Uma M.; Casey, Brian M.; Wapner, Ronald J.; Varner, Michael W.; Rouse, Dwight J.; Thorp, John M.; Sciscione, Anthony; Catalano, Patrick; Saade, George; et al.
Abstract : OBJECTIVE: To evaluate the relationships among excessive gestational weight gain, neonatal adiposity, and adverse obstetric outcomes in women with mild gestational diabetes mellitus. METHODS: This is a secondary analysis of a multicenter randomized clinical trial of women with mild gestational diabetes mellitus. Based on self-reported prepregnancy body weight, gestational weight gain was categorized as excessive if it was greater than 2009 Institute of Medicine guidelines. Maternal outcomes and neonatal anthropomorphic characteristics were compared between women with excessive weight gain and those without excessive weight gain. Multiple linear and logistic regression analyses were performed to adjust for confounding factors. RESULTS: We studied 841 women who participated in the main trial and had prepregnancy body mass index (BMI) and delivery information available (n=431 treatment group, n=410 no treatment). After adjustment for factors including treatment and prepregnancy BMI, excessive weight gain remained associated with large for gestational age (adjusted odds ratio [OR] 2.94, 95% confidence interval [CI] 1.81–4.93), birth weight greater than 4, 000 g (adjusted OR 2.56, 95% CI 1.54–4.40), preeclampsia (adjusted OR 2.96, 95% CI 1.35–7.03), and cesarean delivery for labor arrest (adjusted OR 2.37, 95% CI 1.30–4.44). In addition, excessive weight gain was independently associated with increased total neonatal fat ( P <.001) and birth weight ( P <.001). CONCLUSION: In women with both treated and untreated mild gestational diabetes mellitus, excessive gestational weight gain was independently associated with both greater birth weight and adiposity. Abstract : Supplemental Digital Content is Available in the Text.In women with both treated and untreated mild gestational diabetes mellitus, excessive gestational weight gain is associated with increased frequency of macrosomia and greater neonatal fat mass.